2006
DOI: 10.1287/mnsc.1050.0436
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Causes of the Bullwhip Effect and the Observed Value of Inventory Information

Abstract: The tendency of orders to increase in variability as one moves up a supply chain is commonly known as the bullwhip effect. We study this phenomenon from a behavioral perspective in the context of a simple, serial, supply chain subject to information lags and stochastic demand. We conduct two experiments on two different sets of participants. In the first, we find the bullwhip effect still exists when normal operational causes (e.g., batching, price fluctuations, demand estimation, etc.) are removed. The persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
377
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 461 publications
(399 citation statements)
references
References 33 publications
15
377
2
5
Order By: Relevance
“…In contrast to the theory proposed by Bowman, many researchers have examined managerial behavior using real-life data and laboratory experiments, and found that managers' decisions do not correspond to the expected profit-maximizing decisions due to the complexity of the situation (Deshpande et al 2003, Keizers et al 2003 or some form of decision bias (Schweitzer andCachon 2000, Croson andDonohue 2006). Unlike the settings in these papers, store managers in our setting are provided an automated system and voluntarily choose to deviate from it.…”
Section: Literature Reviewmentioning
confidence: 82%
“…In contrast to the theory proposed by Bowman, many researchers have examined managerial behavior using real-life data and laboratory experiments, and found that managers' decisions do not correspond to the expected profit-maximizing decisions due to the complexity of the situation (Deshpande et al 2003, Keizers et al 2003 or some form of decision bias (Schweitzer andCachon 2000, Croson andDonohue 2006). Unlike the settings in these papers, store managers in our setting are provided an automated system and voluntarily choose to deviate from it.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Earlier experiments show that whether managers and students behave differently depends on the context. Most studies with operations management contexts have shown that the two groups behave similarly (see Croson and Donohue 2006, Bolton et al 2012, Lim and Ho 2007 for examples of beer game, newsvendor, and contracting experiments). In other contexts, experienced professionals are also shown to exhibit similar behavioral biases as observed in lab experiments with student participants (e.g., Cooper et al 1999, Massey andThaler 2013), although evidence to the contrary also exist (e.g., Fehr and List 2004 the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, research in experimental economics has addressed this issue explicitly. Indeed, Dyer, Kagel, and Levine (1989) and Croson and Donohue (2006) find that 'real world' decision makers performed the same or sometimes worse in the laboratory setting than students. Nonetheless, additional research that uses other sampling frames, not just MBA/undergraduate students, would clearly provide additional value to the field.…”
Section: Discussionmentioning
confidence: 99%